1978
DOI: 10.1073/pnas.75.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Syncatalytic conformational changes in aspartate aminotransferase determined by hydrogen-deuterium exchange.

Abstract: Catalysis-linked conformational transitions of aspartate aminotransferase (cytosolic isoenzyme from pig heart; L-aspartate:2-oxoglutarate aminotransferase, EC 2.6.1.1) have been probed by infrared spectrophotometric measurement of hydrogen-deuterium exchange. In the unliganded pyridoxal form of the enzyme at pH 6.0 and 200, 43% of the total 411 peptide hydrogens per subunit exchange within the first 10 min. An additional 9% exchange slowly in the following time period to 360 min. A quite similar exchange curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It has been observed in solution studies (Gehring & Christen, 1978; Pfister et al, 1978) as well as by X-ray crystallographic analyses (Kirsch et al, 1984; C. Almo and A. T. Danishefsky, unpublished results) that the enzyme undergoes a conformational change upon binding dicarboxylic acid substrates or inhibitors. This motion can be modeled, based on crystal structures of the open and closed forms, as a rigid-body rotation of the small domain with respect to the large domain, resulting in the closing of the enzyme around the substrate.…”
mentioning
confidence: 95%
“…It has been observed in solution studies (Gehring & Christen, 1978; Pfister et al, 1978) as well as by X-ray crystallographic analyses (Kirsch et al, 1984; C. Almo and A. T. Danishefsky, unpublished results) that the enzyme undergoes a conformational change upon binding dicarboxylic acid substrates or inhibitors. This motion can be modeled, based on crystal structures of the open and closed forms, as a rigid-body rotation of the small domain with respect to the large domain, resulting in the closing of the enzyme around the substrate.…”
mentioning
confidence: 95%
“…How do lattice forces decrease the catalytic efficiency of the enzyme? Lattice forces must either distort the geometry of the active site or impede ligand-induced or syncatalytic conformational adaptations that are integral features of the catalytic mechanism (Gehring & Christen, 1978;Pfister et al, 1978). A detailed kinetic analysis of crystalline AspAT in conjunction with mechanismbased chemical modifications has even indicated that its measured molar activity corresponds to the mean of two functionally non-equivalent active sites of the crystalline enzyme dimer.…”
Section: Discussionmentioning
confidence: 99%